Development of smart home system based on mobile apps control using IoT for educational purposes - Rosli, Ahmad Asyraf; Muhammad Razif, Muhammad Rusydi; Abu Hassan, Omar; Mohd Shah, Nor Shahida; Mohd Nordin, Ili Najaa Aimi; Mustafa, Khairul Nizam (2021)
The Internet of Things (IoT) with its enormous growth widens its applications to the living environment of the people by changing a home to a smart home. The smart home is a system, which connect homes with various types of digital devices to communicate with each other through the internet. Based on our prior study, 59% of the respondent among Malaysians are unaware about the IoT or just heard about it without knowing its concept. Thus, this project will present a development of a smart home system based on mobile apps control using IoT to educate Malaysian. This project uses a combination of wireless technology and infrared sensor to detect the motion and a microcontroller to control the usage of appliances in the home. Blynk as a mobile app has been programmed and used to control and display the usage of LED, fan and camera. The output of the appliances will be displayed on the Blynk in kind of LED icon and stream video. The IoT system has been successfully developed and able to follow the instruction given. The LED, fan and camera will turn ON when the switch button in Blynk is pressed. The system has a limited range of operation because it depends on the Wi-Fi signal range, which is about 50 meters of the developed smart home using IoT control. The proposed smart home prototype is useful in the education sector to expose all Malaysian to the current technology especially students and staffs in the university.